Effect of Postharvest Soil and Foliar Application of Boron Fertilizer on the Partitioning of Boron in Apple Trees - Sanchez, Enrique Eduardo; Righetti, Timothy L. (American Society for Horticultural Science, 2020)
This study was carried out on mature `Delicious' apple trees (Malus domestica Borkh.) on EM 9 rootstock. Labeled B (99.63 Atom % 10B) was applied as boric acid. Treatments were postharvest foliar B at 375 mg·L–1, postharvest foliar B (375 mg·L–1) plus urea (2.5% wt/vol), and a soil application at the same per-tree rate as the foliar treatments (16 g boric acid/tree). Postharvest foliar B applied with or without urea was efficiently transported from the leaves into storage tissues for the next year's growth. However, soil-applied B remained mostly in the roots while very little was translocated to the above-ground portions of the tree at full bloom. When urea was added to a foliar B spray, the amount of B in the roots and flower clusters increased at full bloom. Although increasing the efficiency of foliar B applications may not be necessary, combining urea and B into a single application is recommended when growers want to apply both N and B. Shoot leaves from all treatments collected late in the season (midsummer) had similar B concentrations, even though treatments altered the amount of added B that was present in different tree tissues early in the season.